The Effect of Fixed Asset Turnover And Quick Ratio on Net Profit Margin in the Property and Real Estate Subsector in Indonesia - Oktafiona, Gebi; Roza, Seflidiana; Nurhayati, Nurhayati (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Net Profit Margin is a metric that indicates the amount of profit generated from each unit of sales revenue. The Quick Ratio is a financial tool used to assess the liquidity position of a company, project, investment centre, or profit centre. Fixed Assets Turnover is a ratio that measures how efficiently funds invested in fixed assets are rotating within a specific timeframe. The main objective of this study is to analyse the impact of Fixed Asset Turnover and Quick Ratio on the Net Profit Margin of Property and Real Estate firms from 2020 to 2022. The research included a total of 62 companies in its population, with a sample size of 52 companies. The data collection methods employed in this study were based on literature review and documentation. In this analysis, classical assumption testing, determination coefficient (R2) testing, multiple linear regression, and hypothesis testing were utilised. The findings indicated that Fixed Asset Turnover had a noteworthy impact on Net Profit Margin, with a t value of 1.771> 1.655 at α 0.01. Testing the third hypothesis using the f test showed that the f statistic of 2.591 was less than the f table value of 3.097, indicating that the Net Profit Margin had no significant impact on Fixed Asset Turnover and Quick Ratio. The variables of Fixed Asset Turnover and Quick Ratio could only account for 5.4% of the Net Profit Margin as per the determination coefficient test results, indicating a low correlation between the dependent and independent variables.